A Methodological Proposal for Pharmacotherapeutic Updating Seminars - Ana María Ramos Cedeño; Regla Lisbel López Guerra; Rubén Darío García Núñez; Yeny Dueñas Pérez; José Demián Rodríguez Medina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
The teaching of pharmacology must comply with the scientific method since the selection of drugs is an ongoing, multidisciplinary and participatory process to be developed based on the efficiency, safety, quality, convenience and cost of drugs. Undergraduate clinical training is based, in most cases, in the development of diagnostic capacities rather than in treatment capacities given that this discipline had been taught, until very recently, by pharmacological groups which has resulted in poor prescriptive skills once students receive their degrees. The curricula emitted by the national group of Pharmacology for 2010-2011 proposes that clinical pharmacology should be taught by health problems. Performing updating Pharmacotherapeutic seminars during internship is a way to link Pharmacology with clinical subjects aimed at increasing students' knowledge on this discipline. In this sense we propose a methodology for the development of these seminars intended to strengthen the prescriptive skills of students.